1988
DOI: 10.1159/000181030
|View full text |Cite
|
Sign up to set email alerts
|

Factors Contributing to the Impairment of Growth in Children with Acute Lymphoblastic Leukemia

Abstract: Growth was studied in 88 long-term survivors of acute lymphoblastic leukemia who had been treated with three different regimens of therapy. The following time periods were evaluated: (1) during therapy; (2) between the end of therapy and the onset of puberty, and (3) between the onset of puberty and the most recent observation. We found: (1) a reduction of height SDS during therapy, related to the irradiation dose used; no significant effect of the duration of the therapy could be established; (2) a normal gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…In our study, catch‐up growth was observed following the end of therapy. Similar conclusions were reached by others using isolated chemotherapy in their protocols 36, chemo‐ and radiotherapy 4,15,37, and chemotherapy associated or not with radiotherapy 6,7,28. This finding suggests an important role for chemotherapy in growth retardation during treatment, since the catch‐up occurred only after complete withdrawal of drugs.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In our study, catch‐up growth was observed following the end of therapy. Similar conclusions were reached by others using isolated chemotherapy in their protocols 36, chemo‐ and radiotherapy 4,15,37, and chemotherapy associated or not with radiotherapy 6,7,28. This finding suggests an important role for chemotherapy in growth retardation during treatment, since the catch‐up occurred only after complete withdrawal of drugs.…”
Section: Discussionsupporting
confidence: 82%
“…Several factors have been shown to affect growth after the treatment of ALL, including the disease itself, gender, age at diagnosis, cytotoxic drug therapy, infection and malnutrition during treatment, and cranial irradiation 3–12. The impact of cranial irradiation with 24 Gy on long‐term growth has been well described 7,13–17, but the impact of lower doses, such as 18 Gy and 12 Gy, on growth are not well established. The role of chemotherapy on growth during the treatment of ALL seems to be well recognized 4,13,18,19, although data for long‐term growth are scarcely available.…”
Section: Introductionmentioning
confidence: 99%
“…This suboptimal growth may be attributed to a combination of direct cytotoxic effects on chondral cells, poor nutrition during cancer treatment, impaired spinal growth due to radiotherapy, GH insufficiency during pubertal growth, or early pubertal development after CI, causing premature acceleration in growth rate and compromising final height by decreasing the time interval available for growth [48,49]. The final short stature observed in irradiated and transplanted young subjects may have caused an underestimation of LS BMD by conventional DXA calculations, which are derived from areal measurements.…”
Section: Discussionmentioning
confidence: 99%
“…The patients were divided into two groups. In order to have matched groups with respect to the time intervals after cessation of chemotherapy, 59 patients [36 boys and 23 girls; median age 11.7 years (range [6][7][8][9][10][11][12][13][14][15][16][17][18][19]] out of 108 were enrolled in the study. The only difference of the two protocols was the dose of corticosteroid during remission-induction chemotherapy: group 1 (n ¼ 30) received ''conventional-dose prednisolone therapy (CDP; prednisolone, 2 mg/kg/day, orally)'' and group 2 (n ¼ 29) received ''high-dose methylprednisone therapy (HDMP; Prednol-L, 900-600 mg/m 2 , orally)'' ( Table I).…”
Section: Patientsmentioning
confidence: 99%
“…The prolonged survival of children with acute lymphoblastic leukemia (ALL) has changed the focus to the various late effects of the disease and its treatment. Possible serious late effects of ALL and its treatment are second cancers, cardiac dysfunction, renal damage, pulmonary toxicity, hearing loss, dental changes, obesity, hypogonadism, growth retardation, and decreased bone mass [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%